Firm Objectives, Controls and Organization The Use of Information and the Transfer of Knowledge within the Firm - Eliasson, Gunnar (Springer Netherlands, 1996)
The actual organization and use of information systems in American, European and Japanese firms are investigated and compared with theoretical conclusions. Finally, following the experimental evolution of the information products over the past twenty years, the results presented indicate that information and communication firms are now starting to offer the kind of business information systems predicted by the analysis. The transformation of business information systems technology can be followed in the Chronicle, which is provided on diskette and which covers the development of modern IT and telecommunications industries. The data are arranged to allow researchers to reconfigure the data according to their own needs
Keywords: Industrial Organization; IT in Business; Economic Theory/Quantitative Economics/Mathematical Methods; Industrial organization; Information technology; Business—Data processing; Economic theory; Informationsmanagement; Unternehmensleitung; Informationssystem; Wissensmanagement; Wissenschaftstransfer